若|x-3|=3-x,则x的取值范围是______ A: x>0 B: x=3 C: x<3 D: x≤3 E: x≥3
若|x-3|=3-x,则x的取值范围是______ A: x>0 B: x=3 C: x<3 D: x≤3 E: x≥3
函数$f(x)={{\text{e}}^{2x-{{x}^{2}}}}$在$x=0$处的$3$次Taylor多项式为 A: $1+2x+2{{x}^{2}}+2{{x}^{3}}$ B: $1+2x+2{{x}^{2}}-4{{x}^{3}}$ C: $1+2x+{{x}^{2}}+\frac{2}{3}{{x}^{3}}$ D: $1+2x+{{x}^{2}}-\frac{2}{3}{{x}^{3}}$
函数$f(x)={{\text{e}}^{2x-{{x}^{2}}}}$在$x=0$处的$3$次Taylor多项式为 A: $1+2x+2{{x}^{2}}+2{{x}^{3}}$ B: $1+2x+2{{x}^{2}}-4{{x}^{3}}$ C: $1+2x+{{x}^{2}}+\frac{2}{3}{{x}^{3}}$ D: $1+2x+{{x}^{2}}-\frac{2}{3}{{x}^{3}}$
设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)
设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)
已知X的概率分布为P(X=1)=0.2,P(X=2)=0.3,P(X=3)=0.5,则(1) E(X)_____(2) E(-X+1)=_____(3)E(X²)=_____
已知X的概率分布为P(X=1)=0.2,P(X=2)=0.3,P(X=3)=0.5,则(1) E(X)_____(2) E(-X+1)=_____(3)E(X²)=_____
若集合A={x|-5<;x<;2},B={x|-3<;x<;3},则A∩B=( ) A: {x|-3<;x<;2} B: {x|-5<;x<;2} C: {x|-3<;x<;3} D: {x|-5<;x<;3}
若集合A={x|-5<;x<;2},B={x|-3<;x<;3},则A∩B=( ) A: {x|-3<;x<;2} B: {x|-5<;x<;2} C: {x|-3<;x<;3} D: {x|-5<;x<;3}
已知E(X)=-1,D(X)=3,求:E[3(X*X-2)]
已知E(X)=-1,D(X)=3,求:E[3(X*X-2)]
设X~U(1,b), E(X)=3,则P(1<;X<;3)=.
设X~U(1,b), E(X)=3,则P(1<;X<;3)=.
求∫x^3*e^-x^2dx
求∫x^3*e^-x^2dx
求微分方程[img=372x60]17da65376dc1787.jpg[/img]的通解。 ( ) A: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 B: C26*exp(3*x) + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 C: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 D: C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6
求微分方程[img=372x60]17da65376dc1787.jpg[/img]的通解。 ( ) A: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 B: C26*exp(3*x) + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 C: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 D: C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6
直接积分法1.∫(3^x)(e^x)dx2.∫e^(3+t)/2dx3.∫[3^x-e^(-x)]e^xdx
直接积分法1.∫(3^x)(e^x)dx2.∫e^(3+t)/2dx3.∫[3^x-e^(-x)]e^xdx